2017
DOI: 10.1123/pes.2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for Bone in Childhood—Hitting the Sweet Spot

Abstract: Public health initiatives that target bone-specific exercise interventions during the pubertal years are likely to be the most effective strategy to harness the increased receptiveness of the growing skeleton to mechanical loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Due to changes in PA habits and behaviors over time, the effects of impact loading on the bone SI were more evident in secondary school, high school, and university periods. However, bone appears to be most responsive to mechanical stress from midpuberty to menarche or during Tanner stages II–IV [24]. Age-related changes in hormonal status and body composition related to the maturity of the participants in different school periods therefore may have influenced the response of the bone SI to different impact-loading PAs.…”
Section: Discussionmentioning
confidence: 99%
“…Due to changes in PA habits and behaviors over time, the effects of impact loading on the bone SI were more evident in secondary school, high school, and university periods. However, bone appears to be most responsive to mechanical stress from midpuberty to menarche or during Tanner stages II–IV [24]. Age-related changes in hormonal status and body composition related to the maturity of the participants in different school periods therefore may have influenced the response of the bone SI to different impact-loading PAs.…”
Section: Discussionmentioning
confidence: 99%
“…Activities that provide a mechanical load to the lower body skeleton can be captured with hip-worn accelerometers calibrated to vigorous-intensity PA (VPA). The research evidence indicates the influence of PA on bone is maturity-dependent; that is, bone mass is accrued at a higher rate during the years surrounding Peak Height Velocity (PHV), and that bone responds optimally to PA during these early adolescent years (approximately age 9-14 yr) (2,3,18).…”
Section: Introductionmentioning
confidence: 99%
“…As bone responds to changes in habitual mechanical loading, exercise is an important strategy to build and maintain bone mass at any stage of life 7 8. Animal research has shown that mechanical loads should be applied in short bouts,9 at high rates10 and frequencies11 and induce high-magnitude bone strains12 13 in order to stimulate bone formation.…”
Section: Introductionmentioning
confidence: 99%